Advancements in understanding substantia nigra hyperechogenicity via transcranial sonography in Parkinson’s disease and its clinical implications - Zhang, Yuan-yuan; Jiang, Xu-hong; Zhu, Pei-pei; Zhuo, Wen-yan; Liu, Li-bin (Frontiers in Neurology, 2024)
Amidst rising Parkinson’s disease (PD) incidence in an aging global population, the need for non-invasive and reliable diagnostic methods is increasingly critical. This review evaluates the strategic role of transcranial sonography (TCS) in the early detection and monitoring of PD. TCS’s ability to detect substantia nigra hyperechogenicity offers profound insights into its correlation with essential neuropathological alterations—namely, iron accumulation, neuromelanin depletion, and glial proliferation—fundamental to PD’s pathophysiology. Our analysis highlights TCS’s advantages, including its non-invasiveness, cost-effectiveness, and ease of use, positioning it as an invaluable tool for early diagnosis and continual disease progression monitoring. Moreover, TCS assists in identifying potential risk and protective factors, facilitating tailored therapeutic strategies to enhance clinical outcomes. This review advocates expanding TCS utilization and further research to maximize its diagnostic and prognostic potential in PD management, contributing to a more nuanced understanding of the disease.